Homeostasis Tubuh - Nasyafa, Syabila Febrilia; Saputra, Oktadoni; Zuraida, Reni (Medula, 2024)
The body has mechanisms at the cellular level to maintain internal balance, called dynamic balance. Even though the external environment undergoes changes, the body continues to operate to prevent deviation from this balance. Environmental changes can affect internal systems, so homeostasis is needed to prevent damage to cells, tissues and organs through regulatory mechanisms. Homeostasis regulation involves local control (paracrine and autocrine responses) as well as reflex control involving the nervous and endocrine systems. Homeostasis is a basic concept of physiology that plays an important role in maintaining internal stability and adaptive responses in the body. The importance of homeostasis lies in the fact that the body's cells and tissues can only remain alive and function efficiently if their internal conditions are maintained properly. All organ systems depend on each other to maintain homeostasis, and changes in one system can affect other body systems. Homeostasis includes the body's ability to maintain a stable internal environment despite changes such as temperature, air, atmospheric oxygen, carbon dioxide levels, physical activity, exposure to toxins, disease, drug therapy, fever, and diet. Disruption of homeostasis can cause dysfunction and loss of control of organs in the body. Several physiological systems are regulated by homeostasis, such as thermoreceptors which regulate body temperature and the role of homeostasis in the endocrine system to regulate hormonal balance and hormone regulation in the body. Homeostasis is influenced by several constant conditions, including body temperature and body fluid balance, which are maintained within predetermined limits (the so-called homeostatic range). Examples of other variables are the pH of the extracellular fluid, the concentration of sodium, potassium and calcium ions, and blood sugar levels. Homeostasis is an automatic process and mechanism carried out by living creatures to maintain constant conditions so that their bodies can function normally, even though changes occur in the environment inside or outside the body.